Penerapan SPAN Pada Pencairan Dana di Kantor Pelayanan Perbendaharaan Negara (KPPN) Pematangsiantar - Vitryani Tarigan; Eva Sriwiyanti; Bagudek Tumanggor (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to find out how the application of the State Treasury and Budget System (SPAN) to the disbursement of funds at the Pematangsiantar State Treasury Service Office (KPPN). Data collection in this study was carried out using primary data sources, namely from interviews, documents and observations. The selection of sources is carried out according to certain criteria in each section. The results of this study indicate that the mechanism for disbursement of funds has been carried out in accordance with the Regulation of the Minister of Finance of the Republic of Indonesia Number 190/PMK.05/2012 concerning Payment Procedures in the Framework of Implementing the State Revenue and Expenditure Budget, and the application of SPAN on disbursement of funds at KPPN Pematangsiantar has been running smoothly. fluent. However, there are some drawbacks caused by system constraints in its application. Constraints faced such as switching SPAN users to the head office, the majority of baby boomers employees, network disturbances and the lack of innovation to create backup databases